Biocompatibility evaluation of dicalcium phosphate/calcium sulfate/poly (amino acid) composite for orthopedic tissue engineering in vitro and in vivo. Issue 11 (23rd July 2016) - Wang, Peng; Liu, Pengzheng; Peng, Haitao; Luo, Xiaoman; Yuan, Huipin; Zhang, Juncai; Yan, Yonggang
Abstract: In vitro cytocompatibility of ternary biocomposite of dicalcium phosphate (DCP) and calcium sulfate (CS) containing 40 wt% poly (amino acid) (PAA) was evaluated using L929 ﬁbroblasts and MG-63 osteoblast-like cells. Thereafter, the biocompatibility of biocomposite in vivo was investigated using an implantation in muscle and bone model. In vitro L929 and MG-63 cell culture experiments showed that the composite and PAA polymer were noncytotoxic and allowed cells to adhere and proliferate. The scanning electron microscope (SEM) confirmed that two kinds of cells maintained their phenotype on all of samples surfaces. Moreover, the DCP/CS/PAA composite showed higher cellular viability than that of PAA; meanwhile, the cell proliferation and ALP activity were much higher when DCP/CS had added into PAA. After implanted in muscle of rabbits for 12 weeks, the histological evaluation indicated that the composite exhibited excellent biocompatibility and no inflammatory responses were found. When implanted into bone defects of femoral condyle of rabbits, the composite was combined directly with the host bone tissue without fibrous capsule tissue, which shown good biocompatibility and osteoconductivity. Thus, this novel composite may have potential application in the clinical setting.